Alih Wahana Puisi ke Braille dan Audiobook di Panti Sosial Bina Netra Tuah Sakato Padang - Devy Kurnia Alamsyah; Nur Rosita; Rila Muspita (Universitas Negeri Padang, 2021)
Literature has become an inseparable part of the history of human civilization. Literature is considered to carry a dual function during its existence; it is not only entertaining (dulce) but it also offers meaning (utile) to life itself. The aesthetic value of using language, essentially, offers a different way of looking at and fostering empathy. In other words, literary texts affect the reader's perception of space which in this case is represented by those whose sense of sight works perfectly—while literature is expected to be present for all. On the other hand, people with visual impairments have limitations in accessing literary works. So a creative solution is needed that is able to bridge this problem. In the community service program carried out at the Bina Netra Tuah Sakato Padang Social Institution, the instructors conducted braille writing training for college students as well as introducing literary works, especially poetry, to the clients there. In addition, an adaptation was carried out through the making of a compilation of braille poetry books and the recording of contemporary poetry in the form of audiobooks to be handed over to the library at the social institution. This paper reviews the program in the “Literature for All” campaign to make it more contextual and accessible to everyone—especially those with visual impairments.